Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm stuck how to evaluate this $$\sum_{j=0}^n \sum_{k=0}^n p_j p_k (-1)^k i^{j+k} $$ where $i = \sqrt{-1}$ and $p_k$ are just variables. Can this be expressed as squares of $p_k$'s like $(p_0 - p_2 + p_4 -p_6 \pm \cdots)^2 + (p_1 - p_3 + p_5 \mp \cdots)^2$?

share|cite|improve this question
$(-1)^ki^{j+k}=i^{j+3k}=i^{j-k}$, so you can write it $\sum_{j=0}^n\sum_{k=0}^np_jp_ki^{j-k}$, but I doubt that this will do any good. – Brian M. Scott Sep 19 '12 at 7:58
up vote 3 down vote accepted

The double sum decomposes into a product of single sums:

$$ \begin{align} \sum_{j=0}^n \sum_{k=0}^n p_j p_k (-1)^k\mathrm i^{j+k} &= \left(\sum_{j=0}^np_j\mathrm i^j\right)\left(\sum_{k=0}^n p_k (-\mathrm i)^k\right)\;. \end{align} $$

If the $p_j$ are real, then this is the squared absolute value of $\sum_jp_j\mathrm i^j$, which is a component of the discrete Fourier transform of the $p_j$ if $4\mid n+1$. For general $p_j$, it's the product of two different Fourier components.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.